Modelling changes in healthcare demand through geographic data extrapolation. Issue 2 (3rd April 2022) - Palmer, Geraint Ian; Harper, Paul; Knight, Vincent; Brooks, Cathy
ABSTRACT: Stay Well Plans are a new programme of care offered to frail and elderly people in Newport. In 2016 a roll out the programme to be offered in all five counties serviced by Aneurin Bevan University Health Board was planned. This paper presents the data analysis and modelling used to determine the programme's effects on the demand of the wider system, and the effects of a Gwent-wide roll out. We extrapolate information from data from a geographical subset of the model domain to a larger geographical area, adjusting for population sizes, deprivation, and distances to healthcare facilities. These parametrise a Markov model and Monte Carlo simulation to predict changes in demand due to different levels of roll out. We conclude that a programme roll out may result in a large reduction on demand at residential care, however at the expense of an increase in demand at community care services.